Macroeconomic Theory and the Eurozone Crisis - Alcouffe, Alain 1945-; Baslé, Maurice; Poettinger, Monika (Routledge Series in the History of Economics, 2020)
The financial crisis of 2007 required the economics discipline to thoroughly re-evaluate its prevailing theories about economic cycles and economic growth. With a focus on Europe, this volume identifies the latest strands of research on business cycles, monetary theory, the evolution of social policies and public spending, and the institutional context of the European Union. It also considers whether these new ideas could have helped us avoid the crisis, and how they might reshape the current economic paradigm.This book will be of interest to advanced students and researchers in European economics, macroeconomics and economic history